2022
DOI: 10.1007/s00381-022-05450-6
|View full text |Cite
|
Sign up to set email alerts
|

EMR adoption in Dhaka, Bangladesh: a template to index pediatric central nervous system tumor care and a review of preliminary neuro-oncologic observations

Abstract: Purpose To describe the design, implementation, and adoption of a simplified electronic medical record (EMR) and its use in documenting pediatric central nervous system (CNS) tumors at a tertiary care referral hospital in South-East Asia. Methods A novel EMR, cataloguing pediatric CNS tumors was used to collect data from August 2017 to March 2020 at National Institute of Neurosciences and Hospital (NINS&H) in Dhaka, Bangladesh. Results Two hundred forty-nine pediatric patients with a CNS tumor were admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…found that there was skepticism among clinical providers and hospital administrators regarding aspects of EMR, thus requiring extensive pre-implementation meetings, focus groups, and discussions to address the feasibility and acceptance of implementing this tool in the hospital ( Dasari et al., 2016b ). Hesitancy among stakeholders was also noted in other articles, pointing out the competing demands on neurosurgeons’ time to use a new system and simply not being prepared to adapt to this system ( Mukherjee et al., 2022 ; Williams and Boren, 2008 ).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…found that there was skepticism among clinical providers and hospital administrators regarding aspects of EMR, thus requiring extensive pre-implementation meetings, focus groups, and discussions to address the feasibility and acceptance of implementing this tool in the hospital ( Dasari et al., 2016b ). Hesitancy among stakeholders was also noted in other articles, pointing out the competing demands on neurosurgeons’ time to use a new system and simply not being prepared to adapt to this system ( Mukherjee et al., 2022 ; Williams and Boren, 2008 ).…”
Section: Discussionmentioning
confidence: 89%
“…A total of 14 articles were included in this scoping review ( Luan et al., 2021 ; Shapiro and Kamal, 2022 ; Ferry et al., 2021 ; Dasari et al., 2016a , 2016b ; Grant et al., 2021 ; Yancey et al., 2019 ; Mukherjee et al., 2022 ; Williams and Boren, 2008 ; Gyedu et al., 2015 ; Spence et al., 2019 ; Meara et al., 2015 ; Rock et al., 2020 ; Quinsey et al., 2018 ) ( Table 4 ). Three overarching themes were identified: (1) the overall benefit of EMR usage is substantial; (2) extreme barriers to implementing EMR systems in LMICs exist; and (3) there is a direct correlation between research efforts and EMR usage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations